Avaliação da injeção de gás HHO em um gerador a gasolina para fins de energização rural - Silveira, Vander Fabio (2012)
This study aimed to develop and evaluate an electrolytic reaction system for the production of HHO gas. The HHO gas, also known as Brown s gas or hydroxyl gas, can be used together with liquid fuel in Otto and Diesel cycle engines, to reduce their consumption. To conduct the study was built an electrolytic reactor with 360L steel plates in an acrylic vat. It was evaluated the performance of the electrolytic reactor, using the electrolytes of sodium hydroxide and potassium hydroxide. The findings allowed to conclude that the reactor showed better energy performance in the production of HHO gas when using sodium hydroxide as electrolyte